Iron lake ebook A novel. - Krueger, William Kent (Cork O'Connor, 1999)
The 20th anniversary edition of the first novel in William Kent Krueger's beloved and bestselling Cork O'Connor mystery series—includes an exclusive bonus short story! "A brilliant achievement, and one every crime reader and writer needs to celebrate." —Louise Penny, #1 New York Times bestselling author of Glass Houses "A master craftsman [and] a series of books written with a grace and precision so stunning that you'd swear the stories were your own." —Craig Johnson, author of the Walt Longmire series "Among thoughtful readers, William Kent Krueger holds a very special place in the pantheon." —C.J. Box, #1 New York Times bestselling author of The Disappeared In eighteen novels over twenty years, William Kent Krueger has enthralled readers with the adventures of P.I. Cork O'Connor, former sheriff of Aurora, Minnesota—selling more than 1.5 million copies of his books and winning the Edgar Award, Minnesota Book Award, Northeastern Minnesota Book Award, Dilys Award, Lovey Award, and Anthony Award along the way. Now, in this special anniversary edition, longtime fans and new readers alike can read the novel that first introduced Corcoran "Cork" O'Connor to the world. Part Irish, part Anishinaabe Indian, Cork is having difficulty dealing with the marital meltdown that has separated him from his children, getting by on heavy doses of caffeine, nicotine, and guilt. Once a cop on Chicago's South Side, there's not much that can shock him. But when the town's judge is brutally murdered, and a young Eagle Scout is reported missing, Cork takes on this complicated and perplexing case of conspiracy, corruption, and a small-town secret that hits painfully close to home.